2017
DOI: 10.1177/1479164117715855
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal-derived hydroimidazolone-1 evokes inflammatory reactions in endothelial cells via an interaction with receptor for advanced glycation end products

Abstract: Our present results indicate that methylglyoxal-derived hydroimidazolone 1 evokes inflammatory reactions in human umbilical vein endothelial cells via receptor for advanced glycation end products, although apparently limited to supraphysiological levels of methylglyoxal-derived hydroimidazolone 1. Methylglyoxal-derived hydroimidazolone 1 is a distinct advanced glycation end product structure that could mediate harmful effects of methylglyoxal and glyceraldehyde-mediated glycation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…This injury was attenuated by pretreatment with 25 μM NGR1, as indicated by a decrease in LDH release. The mechanism that causes cardiac injury by AGEs is reported to be associated with detrimental endoplasmic reticulum stress, inflammation, oxidative stress and mitochondrial damage ( Yang et al, 2015 ; Zhao et al, 2016 ; Ishibashi et al, 2017 ). Consistent with previous literature, in our study, AGEs were found to strongly inhibit H9c2 cell viability accompanied by aggressive ROS and massive apoptosis both in vitro (Figures 2 , 3 ), and in vivo (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…This injury was attenuated by pretreatment with 25 μM NGR1, as indicated by a decrease in LDH release. The mechanism that causes cardiac injury by AGEs is reported to be associated with detrimental endoplasmic reticulum stress, inflammation, oxidative stress and mitochondrial damage ( Yang et al, 2015 ; Zhao et al, 2016 ; Ishibashi et al, 2017 ). Consistent with previous literature, in our study, AGEs were found to strongly inhibit H9c2 cell viability accompanied by aggressive ROS and massive apoptosis both in vitro (Figures 2 , 3 ), and in vivo (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies revealed that the plasma MGO level is significantly increased in diabetic patients and is involved in diabetes-related vascular disorders such as hypertension, nephropathy, and retinopathy [ 28 31 ]. Recently, it indicated that MGO-derived hydroimidazolone-1 evokes inflammatory reactions in human umbilical vein endothelial cells via RAGE [ 32 ]. In our study, we showed an increased MGO level in RA patients and these levels were markedly increased in patients with high activity disease.…”
Section: Discussionmentioning
confidence: 99%
“…This condition frequently leads to increased intracellular levels of MG-derived AGEs, a state known as “glycative stress” [ 1 ]. In turn, glycative stress can lead to increased formation of reactive oxygen species (ROS) [ 2 ], activation of inflammatory pathways through the receptor for AGEs (RAGE) [ 3 ], activation of the mitochondrial pathway of apoptosis [ 4 , 5 ], and induction of epithelial-to mesenchymal transition [ 6 ]. Given that all these biological responses underpin the genesis of several human diseases, MG and MG-derived MG-H1, as well as Glo1, have been proved to play a crucial role in the etiogenesis of many diseases, including cancer [ 7 , 8 , 9 ], infertility [ 5 , 10 ], osteoporosis [ 2 , 11 ], obesity and diabetes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%